TWO NEW RECORDS OF CARANGID FISHES FROM INDIAN SEAS - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Two species of the fishes, belonging to the family Carangidae, Alepesmacrurus (Bleeker) and Carangoides coeruleopinnatus (Ruppell) are reported forthe fatX time from Indian seas. They are briefly described and their systaniaticpositions are discussed